2017
DOI: 10.1016/j.athoracsur.2017.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Calcific Degeneration of CorMatrix 4 Years After Bicuspidization of Unicuspid Aortic Valve

Abstract: We report the long-term outcomes of a 12-year-old boy who underwent bicuspidization of a severely stenotic unicuspid aortic valve with CorMatrix small intestinal submucosal extracellular matrix (CorMatrix Cardiovascular, Roswell, GA). CorMatrix supported favorable immediate surgical and echocardiographic outcomes and maintained stable growing functional dynamics for 2 years. At 52.5 months in situ, however, the valve failed with severe calcification, fibrosis, and retraction necessitating a redo operation. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Interestingly, the literature describing AVrs using CorMatrix do not indicate good outcomes, irrespective of follow‐up time. Hoffman and associates reported significant valve insufficiency in five (83%) pediatric patients at 4 months to a 1‐year follow‐up, Mosala and associates demonstrated similar bad outcomes at 4‐year follow‐up for a pediatric patient requiring a reoperation for valve failure, severe calcification, fibrosis, and retraction 15,16 . Furthermore, the studies comparing CorMatrix and autologous pericardium also reported no significant advantages for CorMatrix from histological, echocardiogram, and clinical data.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, the literature describing AVrs using CorMatrix do not indicate good outcomes, irrespective of follow‐up time. Hoffman and associates reported significant valve insufficiency in five (83%) pediatric patients at 4 months to a 1‐year follow‐up, Mosala and associates demonstrated similar bad outcomes at 4‐year follow‐up for a pediatric patient requiring a reoperation for valve failure, severe calcification, fibrosis, and retraction 15,16 . Furthermore, the studies comparing CorMatrix and autologous pericardium also reported no significant advantages for CorMatrix from histological, echocardiogram, and clinical data.…”
Section: Discussionmentioning
confidence: 97%
“…13,14 Overall, long-term studies using CorMatrix are sparse, but multiple midterm studies and case reports demonstrate poor durability of the scaffold for valvular repair due to progressive inflammation and fibrotic degeneration. 15,16 However, despite multiple studies now cautioning against the use of CorMatrix for long-term repair and the need for reoperation, total resorption of the patch is seemingly rare.…”
Section: Discussionmentioning
confidence: 99%
“… 71 , 72 An inflammatory response comprised of eosinophils, macrophages, and giant cell reactions has been repeatedly demonstrated in explants of CorMatrix and CardioCel. 76 , 80 , 87 In limited observation of a single patient with 2 CorMatrix patches, 1 patch generated a marked inflammatory response while the other did not, indicating that such responses could be tissue specific or related to the surgical procedure. 86 In many but not all cases, explanted xenografts showing inflammation also show fibrosis and calcification, processes that are undesirable for development of true functional neotissues.…”
Section: Allogeneic and Xenogeneic Materialsmentioning
confidence: 99%